Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1523/jneurosci.3060-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Action and Outcome Encoding in the Primate Caudate Nucleus

Abstract: The basal ganglia appear to have a central role in reinforcement learning. Previous experiments, focusing on activity preceding movement execution, support the idea that dorsal striatal neurons bias action selection according to the expected values of actions. However, many phasically active striatal neurons respond at a time too late to initiate or select movements. Given the data suggesting a role for the basal ganglia in reinforcement learning, postmovement activity may therefore reflect evaluative processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
138
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(160 citation statements)
references
References 71 publications
(89 reference statements)
20
138
2
Order By: Relevance
“…By contrast, the parsimonious alternative pro-posed here, whereby in such contexts a decision is made between the stimuli, would not suffer from the same scaling problem. We did not find action value signals (5,12,28) in the SC or AC conditions even at liberal thresholds. A possible explanation for the lack of action value signals could be that, in contrast to previous paradigms, in the current study subjects did not have to keep track of action values over trials and doing so would have not improved performance.…”
Section: Discussioncontrasting
confidence: 83%
“…By contrast, the parsimonious alternative pro-posed here, whereby in such contexts a decision is made between the stimuli, would not suffer from the same scaling problem. We did not find action value signals (5,12,28) in the SC or AC conditions even at liberal thresholds. A possible explanation for the lack of action value signals could be that, in contrast to previous paradigms, in the current study subjects did not have to keep track of action values over trials and doing so would have not improved performance.…”
Section: Discussioncontrasting
confidence: 83%
“…Although these signals are precursors of choice, they are not instances of action values since they are stimulus-based and independent of the action required to obtain them. To date, only three monkey electrophysiology studies have found evidence for the presence of action-value signals for hand and eye movements in the striatum during simple decisionmaking tasks (5)(6)(7). This study extends their findings in three directions.…”
supporting
confidence: 76%
“…First, he needs to assign a value to each action under consideration. These signals, known as action values, encode the value of each action before choice and regardless of whether it is subsequently chosen or not, which allows them to serve as inputs into the decision-making process (5)(6)(7). Second, these action values are compared to generate a choice.…”
mentioning
confidence: 99%
“…However, reasonable candidates include dopaminergic (DA) neurons in the ventral tegemental area (VTA) and the substantia nigra pars compacta (SNc) that might influence activity in visual cortex via direct projections to early areas of visual cortex (Berger et al 1988(Berger et al , 1991Devoto and Flore 2006). However, these projections are generally thought to be sparse, so it is likely that indirect DA signals relayed through the striatum and then to frontal and parietal cortex play an important role in regulating value-related changes in early visual cortex (Barraclough et al 2004;Ding and Hikosaka 2006;Dorris and Glimcher 2004;Gläscher et al 2009;Glimcher 2003;Hikosaka et al 2008;Hollerman and Schultz 1998;Ikeda and Hikosaka 2003;Lau and Glimcher 2007;Leon and Shadlen 1999;Luk and Wallis 2009;Platt and Glimcher 1999;Schultz and Dickinson 2000;Seo et al 2007;Sugrue et al 2004;Wallis and Miller 2003;Watanabe 1996). Indeed, many of the cortical targets of reward signals-such as oculomotor neurons in frontal and parietal cortex-are ideally situated to send modulatory feedback signals to earlier sensory areas so that the cortical representation of high-value stimulus features can be enhanced (Bisley and Goldberg 2003;Ding and Hikosaka 2006;Gold and Shadlen 2007;Serences and Yantis 2006;Shadlen and Newsome 2001).…”
Section: Value and Population Responses In Human Visual Cortexmentioning
confidence: 99%